Hydropower Development and Its Sustainability With Respect to Sedimentation in Nepal - Sangroula, Durga Prasad (Journal of the Institute of Engineering, 2009)
Sustainable hydropower development is the basic for the economic development of Nepal. The current generating capacity of hydropower projects in Nepal is about 600 MW. Despite adequate availability of surface water, several water resources projects have not been yielding expected output primarily due to sedimentation problems, which were underestimated at design stage in most of the cases. Sediment production in Nepalese watersheds has generally been acknowledged to be the highest in the world and little reliable data of actual sediment production is available. Attempts were made to study the sedimentation processes in the Kulekhani Reservoir, Nepal and efforts were made to find appropriate sediment management options to keep Kulekhani Reservoir Sustainable. This paper provides historical development of hydropower, opportunities and challenges in this sector. Problem associated with sediments in developing hydropower has been addressed. Key words: Hydropower, sedimentation, sediment monitoring, sediment study and research. Journal of the Institute of Engineering, Vol. 7, No. 1, July 2009, pp. 56-64 doi: 10.3126/jie.v7i1.2063